ENCRYPTION AS AN OBSTACLE FOR CRIMIMANL INVESTIGATION AND EVIDENCE COLLECTION - Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Encryption has become an integral part of modern life. It is without a doubt of great importance for the realization of some of the basic human rights in the ubiquitous technical environment, for the daily use of numerous online services, as well as for the functioning of the Internet in general. On the other hand, the authorities in charge of detecting and proving crime are increasingly facing obstacles when accessing encrypted content. Namely, encryption represents a kind of challenge in the implementation of both general and special evidentiary actions. This paper is dedicated to understanding the technical aspects of this challenge. The author explains the basic principles on which encryption technology is based, pointing out the difference between symmetric and asymmetric encryption, between encryption of stored data and data encryption in transit, and between server-based and user-based encryption, and its implication for investigation of crime.